Utricularia kamarudeenii (Lentibulariaceae): a new species from Kerala, India - Arya, Sindhu; Raju, Reshma; Arunraj, Parappurakkal Thazhe; Vishnu, Walsan Kalarikkal; Biju, Punnakot; Anilkumar, Venugopalan Nair Saradhamma (Phytotaxa, 2020)
A new species of Utricularia named U. kamarudeenii, from the paddy fields of Kottayam district of Kerala, India, is described and illustrated. The new species resembles U. aurea but differs from it in the length of spur with respect to lower lip, deeply bilobed lower lip, presence of one type of trap having basal mouth without appendages and hexagonal shape of the seed.